Addressing the associative stigma of psychiatry and psychiatrists: a survey on the attitudes of medical and nursing students and doctors in Verona, Italy - Lasalvia, Antonio; Benedetti, Lorenzo; Bodini, Luca; Albasini, Francesco; Chiamulera, Cristiano; Fabene, Paolo; Rugiu, Carlo; Bonetto, Chiara (BMC Psychology, 2025)
Negative societal attitudes toward mental health often contribute to misconceptions and stereotypes about psychiatry, a phenomenon known as “associative stigma”. This stigma can hinder collaboration between psychiatrists and other specialists and deter students from pursuing psychiatry as a career. This study focused on one of the three main components of stigma by examining attitudes toward psychiatry and psychiatrists among medical and nursing students, as well as doctors, and identifying factors that influence these attitudes. A cross-sectional survey was conducted among medical and nursing students at the University of Verona and doctors affiliated to the Medical Professional Association of Verona. Attitudes toward psychiatry were assessed using the Attitude to Psychiatry Scale. Regression analysis evaluated the relationship between participants’ characteristics and their attitudes toward psychiatry and psychiatrists. A total of 511 medical students, 394 nursing students, and 638 doctors participated in the study. While students had generally positive attitudes towards psychiatry, they perceived it as lacking full respect within medial community (84% medical, 76% nursing), having low prestige (63.5% medical, 65.9% nursing), and receiving insufficient encouragement in university courses (39% medical, 41.7% nursing). Doctors also expressed positive attitudes, though to a lesser extent than students. Their primary concerns related to patient care: 81% reported feeling emotionally drained when treating psychiatric patients, and 58.2% felt that patients were not appreciative of the care received. Female students and doctors, students who had taken psychiatric courses, and doctors in non-surgical specialties exhibited more positive attitudes. This study revealed generally positive attitudes towards psychiatry, underscoring its relevance as a medical specialty. However, concerns regarding the discipline’s perceived status and respect within the medical field highlight areas for targeted interventions to enhance its image and encourage greater interest among students and professionals.
Gesehen am 12.06.2025